Management of Symptomatic Meckel's Diverticulum in Infants and Children - Ghritlaharey, Rajendra K. (Annals of the National Academy of Medical Sciences (India), 2021)
Objectives The primary objective of the present study was to review the demographics of infants and children operated upon for Meckel's diverticulum. The secondary objectives were to review the clinical characteristics, surgical procedures performed, postoperative complications, and the outcome.Materials and Methods This study is a single-institutional, retrospective study and descriptive in nature. It consisted of infants and children below 12 years who were operated upon for Meckel's diverticulum at the author's institute and included data from January 1, 2000 to December 31, 2020.Results Eighty-four children below 12 years were operated upon for Meckel's diverticulum during the study period. The ratio for males to females was 3:1. This study consisted of infants, (n = 22, 26.19%), children of 1 to 5 years of age (n =19, 22.61%), and children of 6 to 12 years of age (n = 43, 51.19%). Clinically, children with Meckel's diverticulum presented in the following order of frequency: (1) intestinal obstruction (n = 59, 70.23%), (2) perforation peritonitis (n = 17, 20.23%), (3) lower gastrointestinal bleeding (n = 4, 4.76%), and (4) incidental finding (n = 4, 4.76%). In 35 (41.66%) children, bowel gangrene was detected. One-fifth (n = 17) of Meckel's diverticulum was responsible for the secondary intussusception. The surgical procedures were performed in the following order of frequency: (1) resection of Meckel's diverticulum, an adjacent segment of ileum and ileoileal anastomosis (n = 36, 42.85%); (2) Meckel's diverticulectomy (n = 32, 38.09%); (3) resection of Meckel's diverticulum, an adjacent segment of ileum with or without cecum and an ileostomy (n = 12, 14.28%); and (4) resection of Meckel's diverticulum, an adjacent segment of ileum, cecum, part of the colon, and ileocolic anastomosis (n = 4, 4.76%). In 8 (9.52%) children, complications were documented during the postoperative period. The present study observed three (3.57%) deaths during the postoperative period.Conclusion Meckel's diverticulum was one of the common causes of acute intestinal obstruction in infants and older children. Ninety percent of children with Meckel's diverticulum presented with features of an acute abdomen. Forty percent of children evidenced bowel gangrene during the surgical procedures. In these children, early diagnosis, timely referral, and institution of surgical therapy for acute abdomen/intestinal obstruction may prevent the development of bowel gangrene and the requirement of bowel resections to some extent.
Keywords: children; infants; intestinal obstruction; intussusception; Meckel's diverticulum; Meckel's diverticulectomy; perforation peritonitis